Memories of Africa, Home, and Abroad in the United States - Olayombo Raji-Oyelade (Yoruba Studies Review, 2023)
There are certain books that will continue to be relevant to contemporary discourse as it fashions themselves out of history, Toyin Falola’s book, Memories of Africa, Home, and Abroad in the United States, is one of those. In the abyss of ‘remembering’ and ‘recollecting’, Falola takes his readers through a seamless journey in the collection of essays and selected images that make up the entirety of his book by exploring the experiences of African migrants through a recount of their memoirs. Thus, memoir is the lens through which Falola challenges normative linear narratives of African history to provide a more complex understanding of the African continent through the creation of complicated stories of African migrants and their lived experiences.